2020
DOI: 10.1111/eth.13070
|View full text |Cite
|
Sign up to set email alerts
|

There is no place like home: Larval habitat type and size affect risk‐taking behaviour in fire salamander larvae (Salamandra salamandra)

Abstract: Individual life histories are strongly influenced by early environmental conditions and experiences. They shape morphology as well as behaviour and can promote adaptive divergence and phenotypic plasticity with regard to different habitat types. The fire salamander (Salamandra salamandra) in the Kottenforst forest in Bonn, Germany, exhibits two genetically distinct ecotypes occurring in two larval habitats, either ponds or streams. In this study, we investigated whether both ecotypes differ in risk‐taking beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…These results indicate that fire salamander larvae had the ability to modulate their behavior depending on immediate predation risk and past variation of environmental conditions. While Oswald et al (2020) showed that risk-taking behavior of salamander larvae depends on the predation risk in the natal habitat, the results presented in this study show that risk-taking behavior is complex and depends on multiple environmental conditions. More generally, while it is well understood that the growth/predation risk trade-off is determined by an interaction between food level and risk, our results indicate that the interactions with environmental factors may modulate the trade-off.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These results indicate that fire salamander larvae had the ability to modulate their behavior depending on immediate predation risk and past variation of environmental conditions. While Oswald et al (2020) showed that risk-taking behavior of salamander larvae depends on the predation risk in the natal habitat, the results presented in this study show that risk-taking behavior is complex and depends on multiple environmental conditions. More generally, while it is well understood that the growth/predation risk trade-off is determined by an interaction between food level and risk, our results indicate that the interactions with environmental factors may modulate the trade-off.…”
Section: Discussionmentioning
confidence: 54%
“…The aim of our study was to investigate the interactive effects of the long-term exposure to contrasting food levels and light conditions on the antipredator response in larvae of the fire salamander (Salamandra salamandra). We used the probability to emerge from the refuge and the distance moved outside the refuge as antipredator responses describing risk-taking behavior (Sih et al 1988, Anholt and Werner 1995, Oswald et al 2020. Specifically, we hypothesized that long-term exposure to low food levels coupled with longer photoperiod would decrease antipredator response in prey (i.e., larvae will emerge from the refuge more frequently and travel longer distances) when exposed to cues from a predator.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions impact small individuals more than larger individuals (Feder, 1983;Pastorelli et al, 2007), especially when these threats are combined (Rohr and Madison, 2003). Although body size has been associated with exploratory behaviour in amphibians (Keheller et al, 2017), to our knowledge, the present results provide one of the first evidences of a positive relationship between boldness and body size in salamanders (Oswald et al, 2020). This relationship has been already described in other heterothermic vertebrates with continuous body growth such as snakes (Maillet et al, 2015;Mayer et al, 2016) and fish (Harris et al, 2010).…”
Section: )mentioning
confidence: 44%
“…Because there was a significant repeatability between trials, an individual mean "boldness" value was calculated as: [log(emergence time in trial 1) + log(emergence time in trial 2)]/2. These nonnormally distributed scores were correlated to individual body size (SVL) by means of Spearman's non-parametric rank test (Oswald et al, 2020). Statistical analyses were performed using Minitab software, version 17.0.…”
mentioning
confidence: 99%
“…Salamanders from the two genetic clusters may have already evolved specific behavioural adaptations to their habitat (Weitere et al, 2004). For instance, females from the two clusters differed in their larval deposition behaviour (Caspers et al, 2015) and larvae from the two habitats differed in their risk-taking behaviour (Oswald, Tunnat, Hahn, & Caspers, 2020). Our study system allows to examine if and how individuals from two habitat types behave differently.…”
Section: Introductionmentioning
confidence: 99%